The fade of fossil fuel power stations in Southwestern Europe: industrial built heritage considerations on climate change policies - Jorge Magaz-molina; Ángeles Layuno Rosas; Júlia Faria (Built Heritage)
Abstract This article addresses the gap in comprehensive studies on the impact of climate change policies on the built heritage of greenhouse gas emitting industries, focusing on the preservation of fossil fuel power stations (FFPSs) in Southwestern Europe. Through a cultural policy review and an extensive survey of FFPSs across Spain, France, Portugal, Italy, Gibraltar, Malta, Monaco, and the Vatican City, the study examines their conservation status and explores heritage-related concerns arising from their closure due to decarbonisation initiatives. The methodology combines the construction of a geo-referenced database using historical references with a multilingual review of heritage literature, administrative reports, and corporate documentation on industrial heritage management and decarbonisation policies. Findings reveal that the preservation of FFPSs affected by decarbonisation programmes is hindered by limited recognition of their cultural values, with economic factors further impeding efforts to prevent demolition and promote conservation. The discussion highlights disparities in the attention given to FFPSs: reused facilities, predominantly located in urban areas and dating to the first half of the 20th century or earlier, contrast sharply with those built in rural or isolated regions since the mid-20th century which face greater conflicts when proposed as heritage assets. This study underscores the challenges and inequities in preserving FFPSs as part of the industrial built heritage affected by decarbonisation policies.